THE SEMANTIC FIELD OF “LOVE” IN JAVANESE LANGUAGE - Hendryanto, Larasati Mauli Amane; Widhyasmaramurti, Widhyasmaramurti (International Review of Humanities Studies, 2024)
This research delves into the extensive lexicon of the Javanese language, specifically focusing on expressions related to feelings of love. The presence of multiple Javanese lexicons denoting love poses a significant challenge, prompting the central question: What are the semantic nuances that distinguish each lexicon, given the absence of absolute synonyms? The research aims to elucidate the semantic fields that differentiate each love-related lexicon in Javanese. Data for this research is drawn from four distinct Javanese dictionaries, spanning various publication periods. Additionally, the study incorporates diverse data sources, including a book titled "Antologi Cerita Pendek Bahasa Jawa di Yogyakarta," Djaka Lodhang magazine, and the Javanese language corpus from the Javanese Studies at the Faculty of Humanities, Universitas Indonesia which contribute valuable data on sentences conveying the meaning of love. This qualitative research used Nida’s (1975) theoretical framework on componential analysis of meaning. The results show the existence of sixteen Javanese lexicons conveying the meaning of love, with only eight being actively used in sentences, and one common component, four diagnostic components, and forty-one supplementary components. These meaning components provide insights into the nuanced distinctions and potential redefinitions of each love-related lexicon in the Javanese language.